Adsorption of Volatile Organic Compounds (VOCs) on Oxygen‐rich Porous Carbon Materials Obtained from Glucose/Potassium Oxalate. Issue 9 (30th March 2021) - Wang, Huijun; Gao, Jie; Xu, Xiang; Liu, Baogen; Yu, Lingyun; Ren, Yadong; Shi, Rui; Zeng, Zheng; Li, Liqing
Abstract: To investigate the effects of oxygen‐containing functional groups on the adsorption of volatile organic compounds (VOCs) with different polarity, oxygen‐rich porous carbon materials (OPCs) were synthesized by heat treatment of glucose/potassium oxalate material. The carbon material had a large specific surface area (1697 m 2  g −1 ) and a high oxygen content (18.95 at.%). OPC exhibited high adsorption capacity of toluene (309 mg g −1 ) and methanol (447 mg g −1 ). The specific surface area and total pore volume determined the adsorption capacity of toluene and methanol at the high‐pressure range, while the oxygen‐containing groups became the main factor affecting the methanol adsorption at the low‐pressure range due to the hydrogen bond interaction through the density functional theory (DFT) calculations. This study provides an important hint for developing a novel O‐doped adsorbent for the VOCs adsorption applications and analyzing the role of oxygen‐containing groups in the VOCs adsorption under the low‐pressure range. Abstract : In this work, oxygen‐rich porous carbon (OPC) was synthesized by heat‐treating a mixture of glucose and potassium oxalate to explore the effect of O‐containing functional groups on the adsorption of volatile organic compounds (VOCs). The carbon material we obtained had a larger specific surface area and a higher oxygen content. By comparing the adsorption effect of OPC on VOCs, we found that oxygen‐containing functional groups have become the main factor affecting the methanol adsorption capacity of OPC at low pressure.